ANALISIS PENDAPATAN KEDELAI (Glicine max L) DI DESA KUNYIT KECAMATAN BAJUIN KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Subhan Fitriadi; Eddy Triatmoko; Taufik Hidayat (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
The purpose of this research is to know the revenue,the eksplicit cost and the income of Soya Bean Anjosmoro variety farming. This research was conducted in October to December 2014 at Kunyit Village Bajuin Sub District ,Tanah Laut District . The sensus metode used was by observing 6 farmers in Bajuin Village who planted variety anjosmoro . The Average result of the revenue is Rp. 15.264.000,00 farmer-1, the average explicit cost is Rp.10.196.495,67 farmer-1, and the average income is Rp 5.067.504,33 farmer-1 or Rp,- 4.445.179,24 ha-1. From this result of development of farming kedelai variety anjosmoro we believe that it has good prospect and revenue,tecnically and economically.